2017
DOI: 10.3892/etm.2017.5241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apigenin on the expression levels of B‑cell lymphoma‑2, Fas and Fas ligand in renal ischemia‑reperfusion injury in rats

Abstract: The aim of the present study was to investigate the effect and possible mechanism of apigenin on renal ischemia-reperfusion (I/R) injury in rats, as well as in in vitro experiments. In total, 36 rats were subjected to 45 min of renal ischemia, with or without treatment prior to ischemia with different concentrations of apigenin (2, 10 and 50 mg/kg) administered intravenously. All rats were sacrificed at 24 h after I/R injury. The serum creatinine (Cr) and blood urea nitrogen (BUN) levels were analyzed, and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…We also found that the mRNA expression levels of the Fas and Fasl genes in the OSO group were upregulated. Our data are consistent with those of Liu et al ., 61 who reported that increased Fas / Fasl expression could cause kidney damage in rats. In addition, the caspase gene family is essential in maintaining homeostasis by regulating the occurrence of cell death and inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the mRNA expression levels of the Fas and Fasl genes in the OSO group were upregulated. Our data are consistent with those of Liu et al ., 61 who reported that increased Fas / Fasl expression could cause kidney damage in rats. In addition, the caspase gene family is essential in maintaining homeostasis by regulating the occurrence of cell death and inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…PI3K/Akt signaling pathway regulates renal repair after I/R injury, and apigenin (20 mg/kg) pretreatment has been shown to protect against renal I/R injury and prevent tubular apoptosis in vitro and in vivo by activating PI3K/Akt-mediated mitochondria-dependent apoptotic signaling pathway [61]. In addition, inhibition of renal apoptosis by suppressing the activation of the Fas/FasL pathway may be another protective mechanism of apigenin against renal I/R injury [62]. Furthermore, genistein (15 mg/kg) was shown to exert its antiapoptotic and proliferative effects via the SIRT1/p53 axis, and thus ameliorates I/R-induced renal injury [6].…”
Section: Anti-cell Deathmentioning
confidence: 99%
“…Bcl-2, an antiapoptotic protein, is an important factor in determining whether apoptosis occurs and the severity of apoptosis [29,30]. A study by Liu et al [31] In addition, VEGF, an effective trigger of angiogenesis, can change the microcirculation and improve survival and regeneration of neurocytes through angiogenesis in ischemic tissues [33]. Increasing evidence has shown that the combination of VEGF and its receptors can trigger multiple downstream signals and promote angiogenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, an antiapoptotic protein, is an important factor in determining whether apoptosis occurs and the severity of apoptosis [ 29 , 30 ]. A study by Liu et al [ 31 ] indicated that apigenin could inhibit cell apoptosis by increasing the expression level of Bcl-2, thus protecting renal I/R injury. Another study also showed that Radix Ilicis Pubescentis total flavonoids could alleviate cerebral I/R injury via increasing the Bcl-2 protein expression and enhancing the antiapoptotic ability of neurocytes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%